2019
DOI: 10.31883/pjfns/112276
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Wild Strains of Lactobacilli During Kombucha Fermentation and Their Contribution to Functional Characteristics of Beverage

Abstract: beverage has a mild vinegar taste [Chen & Liu, 2000]. In order to obtain a pleasantly sour, sweetened beverage, fermentation should be terminated when titratable acidity (TA) of fermentation broth reaches 4-4.5 g acetic acid/L, that is confi rmed by Kombucha consumers [Cvetković et al., 2008]. The tea fungus is a consortium of acetic acid bacteria (AAB) (Gluconacetobacter xylinum, previously known as Acetobacter xylinum, which is the primary and best studied bacteria in Kombucha) and yeasts (species of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…According to the results presented in the three-dimensional plot (Figure 1b), it can be concluded that the TA value is equally achieved at medium values of fermentation time and any values of tea concentration. The obtained result for pH and TA value is in correlation with the results of Cvetković et al [37] which suggested that after three days of incubation the pH value of 3.21 and TA value of 4.32 g/L can be achieved. The accuracy of the ANN model could be visually assessed by the dispersion of points from the diagonal line in the graphics presented in Figure 2.…”
Section: Figuresupporting
confidence: 88%
See 1 more Smart Citation
“…According to the results presented in the three-dimensional plot (Figure 1b), it can be concluded that the TA value is equally achieved at medium values of fermentation time and any values of tea concentration. The obtained result for pH and TA value is in correlation with the results of Cvetković et al [37] which suggested that after three days of incubation the pH value of 3.21 and TA value of 4.32 g/L can be achieved. The accuracy of the ANN model could be visually assessed by the dispersion of points from the diagonal line in the graphics presented in Figure 2.…”
Section: Figuresupporting
confidence: 88%
“…Furthermore, in vessels whose specific interfacial surface area is 0.3 cm -1 , an optimal acidity of kombucha was achieved practically twice as faster compared to vessels with a specific area of 0.06 cm -1 under the same other experimental parameters (by comparing experiments 5 and 6, as well as 7 and 8 in Table 2). Cvetković et al [37] previously established a mathematical model to ensure the scaling-up process of kombucha fermentation, which can be quite complex and should take into account the specific interfacial area as the main variable. Similar conclusions are reported by Junker [38] and Villarreal-Soto et al [39] which demonstrated the same behaviour during the variability of this operating parameter.…”
Section: Resultsmentioning
confidence: 99%
“…LAB isolated from kombucha are considered potential probiotics since they meet most of the probiotics criteria, e.g., bacteriocin production and bile salt tolerance, in according to the FAO/WHO Guidelines for the Evaluation of Probiotics in Food (2002) (Matei et al, 2018;Pei et al, 2020;Vargas et al, 2021). Incoming LAB easily become community members (Zaets et al, 2016;Cvetković et al, 2019;Bueno et al, 2021) and improve kombucha's biological properties, e.g., antibacterial and antioxidant activities (Nguyen et al, 2015). Another approach is to design rationally assembled (Metchnikoff, 1908), and because of him, fermented milk products entered the daily diet.…”
Section: Rationally Assembled Kombucha Microbial Community Could Support Astronaut Health Long-term Space Missionsmentioning
confidence: 99%
“…Another alternative to dairy probiotics can be modified kombucha, which originally is a fermented tea beverage, prepared by fermenting sweetened black tea with tea fungus, yeasts, and acetic acid bacteria. A study of Cvetković et al [2019] showed the potential of wild strains of LAB in kombucha preparation, without affecting the activity of tea fungus, thus forming grounds for the development of a new, probiotic beverage. Furthermore, fermented fruits can also be a source of prebiotics.…”
Section: Pro-and Prebiotic Activitymentioning
confidence: 99%